The Influence of Product Bundling and Perceived Value on Continuance Intention through the Satisfaction of Non-Subsidized KPR Debtors Bank BTN Medan Branch Office - Siregar, Ahir Diana Putri; Ginting, Paham; Gultom, Parapat (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of product bundling and perceived value on continuance intention through satisfaction among non-subsidized mortgage debtors at Bank BTN, Medan Branch. Using a quantitative approach with 81 respondents selected purposively from 417 debtors, data were collected via questionnaires and analyzed using SEM-PLS. The results show that product bundling has a positive but not significant effect on satisfaction and continuance intention. In contrast, perceived value significantly affects both satisfaction and continuance intention. Satisfaction also significantly influences continuance intention. Additionally, perceived value has a significant indirect effect through satisfaction, while product bundling does not. These findings highlight the critical role of perceived value and satisfaction in encouraging continued use of banking services.